Problematika Indivisibility Digital Assets Pewarisan: Tantangan Hukum Dan Mekanisme Pembagian Dalam Hukum Perdata Indonesia - Rayi Kharisma Rajib; RB. Dhafi Rahadyan Surya Atmaja; Berlina Fatimatuz Zahrani (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The advancement of digital technology has given rise to new forms of wealth  including digital platforms, cryptocurrencies, Non-Fungible Tokens (NFTs), and digital wallets  that hold significant economic value yet lack explicit recognition under Indonesian civil law. This study aims to analyze the legal standing of digital assets within Indonesia's property law framework and to identify the legal problems arising from the indivisibility of digital assets in the context of inheritance, particularly the technical and conceptual obstacles stemming from the absence of comprehensive legal regulation. The research employs a normative juridical method with statutory, conceptual approaches, and comparative approach with different statute and judicial decision. The findings indicate that digital assets may be classified as intangible property (onlichamelijke zaken) under Article 503 of the Civil Code and are therefore inheritable in principle. However, the inherent indivisibility of certain digital assets creates structural challenges for estate distribution, as the Civil Code provides no mechanism for dividing intangible assets that are technically indivisible. The absence of specific regulation generates a legal vacuum (vacuum iuris) that risks prejudicing the rights of heirs.